Study of the combined effects of oxidation and adsorption process in removing MTBE from wastewater - Teoh, Tze Yang (2010)
Treatment of Methyl Tert-Butyl Ether (MTBE) from wastewater supplies presents specific challenges due to the physicochemical properties of MTBE which depend strongly on its hydrophilic nature, and translate into a high solubility in water. MTBE has very low Henry‘s constant and very low affinity for common adsorbents. An investigation was carried out for the treatability of metyl tert-butyl ether (MTBE) in synthetic wastewater. In this research, experimental rig and bench-scale studies using granular activated carbon (GAC) and hydrogen peroxide (H2O2) were conducted to observe the treatability of MTBE in synthetic wastewater. An experimental rig was built up that consist of three conjugated system. Subsequently, MTBE was amended to the H2O2 and air flow, followed by adsorption treatment with GAC. Generally, the major finding suggests that the longer cycle pulsation time (3 minutes open valve + 5 seconds closed valve) with air flow rate at 6 L/min over the synthetic wastewater caused a greater removal of MTBE. The result of this study can help to provide specific guidance into process parameter selection for treating MTBE in wastewaters. The optimum operating conditions are very important for treating the wastewater effectively in a larger scale.